Segmentation of British Sign Language (BSL): Mind the gap!. Issue 4 (April 2015) - Orfanidou, Eleni; McQueen, James M.; Adam, Robert; Morgan, Gary
This study asks how users of British Sign Language (BSL) recognize individual signs in connected sign sequences. We examined whether this is achieved through modality-specific or modality-general segmentation procedures. A modality-specific feature of signed languages is that, during continuous signing, there are salient transitions between sign locations. We used the sign-spotting task to ask if and how BSL signers use these transitions in segmentation. A total of 96 real BSL signs were preceded by nonsense signs which were produced in either the target location or another location (with a small or large transition). Half of the transitions were within the same major body area (e.g., head) and half were across body areas (e.g., chest to hand). Deaf adult BSL users (a group of natives and early learners, and a group of late learners) spotted target signs best when there was a minimal transition and worst when there was a large transition. When location changes were present, both groups performed better when transitions were to a different body area than when they were within the same area. These findings suggest that transitions do not provide explicit sign-boundary cues in a modality-specific fashion. Instead, we argue that smaller transitions help recognition in a modality-general way by limiting lexical search to signs within location neighbourhoods, and that transitions across body areas also aid segmentation in a modality-general way, by providing a phonotactic cue to a sign boundary. We propose that sign segmentation is based on modality-general procedures which are core language-processing mechanisms.